2013
DOI: 10.1002/mar.20644
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Food‐Related Values on Food Purchase Behavior and the Mediating Role of Attitudes: A Swiss Study

Abstract: Personal values and attitudes can help to explain food choice. This study confirmed a hierarchical organization of the value–attitude–behavior chain: Food‐related values influence attitudes, and these, in turn, impact behavior. Contrary to previous findings, values are only partially mediated by attitudes: Some food‐related values are fully mediated, whereas others are partially mediated, and still others have exclusively direct effects on purchase behavior. Questionnaire data from a roughly representative sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 49 publications
6
56
0
1
Order By: Relevance
“…A significant change in organic buying behavior was just apparent, if—in addition to the gain of trust and/or knowledge—at least one price barrier was lowered significantly. This supports previous results that showed that a transparent depiction of food production lowers value–price sensitivity, and as a result, purchase of organic groceries is increased (Bodini et al., ; Hauser et al., ). This is likely because inferences are drawn between various attributes (e.g., organic feature and value for money) prior to evaluating other alternatives (Gruber et al., ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A significant change in organic buying behavior was just apparent, if—in addition to the gain of trust and/or knowledge—at least one price barrier was lowered significantly. This supports previous results that showed that a transparent depiction of food production lowers value–price sensitivity, and as a result, purchase of organic groceries is increased (Bodini et al., ; Hauser et al., ). This is likely because inferences are drawn between various attributes (e.g., organic feature and value for money) prior to evaluating other alternatives (Gruber et al., ).…”
Section: Discussionsupporting
confidence: 91%
“…Certainly, shopping is habitualized (Aertsens, Verbeke, Mondelaers, & Van Huylenbroeck, ) and the extent of an information search depends, among others, on the involvement, the ease of processing available information, and its understanding (Peter, Olson, & Grunert, ). While not all advantages and disadvantages are weighed within a purchase decision (Hauser, Nussbeck, & Jonas, ), Tarkiainen and Sundqvist () see involvement as a crucial key construct because it affects “consumer search and evaluation activities, which are the critical first steps in buying” (p. 845). Recent research revealed that organic buying ratios differ across product categories (Henryks et al., ) and “the effects of promotions vary across … product categories” (Ngobo, , p. 98).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, as value‐attitude‐behavior model (Homer & Kahle, ; Kahle, ; Hauser et. al., ; Shim & Eastlick, 1998) suggests the link might not be that straightforward.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Out of these, values and attitudes are important guiding forces in human life in general as well as in the food context (Hauser, Nussbeck, Jonas, 2013). However, consumption is not always an individual phenomenon, but includes social aspects such as shopping for the family, love and sacrifice, shared social cognition and feelings, influences from social norms, social identity, social situations or group influences (Olsen, Grunert, 2010).…”
Section: Introductionmentioning
confidence: 99%